2016
DOI: 10.1039/c6fo00667a
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory activity of glycopeptides from Paecilomyces sinensis under normal and cyclophosphamide induced immunosuppressive conditions in mice models

Abstract: The present study was designed to evaluate immune-modulating effects of the glycopeptide from Paecilomyces sinensis (CPS-II) by using mouse peritoneal macrophage and cytoxan (CTX) induced immunosuppression models. Our results from phagocytotic and mononuclear phagocytic system function assays showed that CPS-II stimulated phagocytosis of the phagocytes. A splenocyte proliferation assay showed that CPS-II acted to combine Concanavalin A (ConA) or lipopolysaccharides (LPS) in splenocyte proliferation. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Thus, Cy was used to creating the immunosuppressed animal model in this study. Cy-induced immunosuppressed mice exhibited significantly lower body weight gain, spleen index, and cytokine levels (IFN-γ, IL-2, IL-6, and TNF-α) compared to the control group [24]. Similar changes were also shown in the present Cy-induced mouse model, indicating that the immunosuppression model was built successfully.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, Cy was used to creating the immunosuppressed animal model in this study. Cy-induced immunosuppressed mice exhibited significantly lower body weight gain, spleen index, and cytokine levels (IFN-γ, IL-2, IL-6, and TNF-α) compared to the control group [24]. Similar changes were also shown in the present Cy-induced mouse model, indicating that the immunosuppression model was built successfully.…”
Section: Discussionsupporting
confidence: 80%
“…The spleen is an important immune organ in the body and an important place of differentiation of the thymocytes in the lymphocyte (Z. Y. Zhu, Meng, Sun, et al, ). These lymphocytes are the major effector cells in the mammalian immune system and a component of cell‐mediated response.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen contains a large number of lymphocytes, including B-lymphocytes and T-lymphocytes, which play an important role in humoral and cellular immunity. We investigated the proliferative capacity of B-and T-lymphocytes that were stimulated by LPS and ConA to evaluate changes in the immune response [22]. The results showed that KG effectively enhanced the proliferative capacity The results of KG-24 administration were not as promising as those of KG-6.…”
Section: Discussionmentioning
confidence: 99%